Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $X_1$ and $X_2$ be particles of mass $m_1$ and $m_1$, where $X_1$=$(x_1^1,x_2^1,x_3^1)$ and $X_2$=$(x_1^2,x_2^2,x_3^2)$. The potential energy of this system is $U=gm_1m_2/|X_2-X_1|)$ and $\operatorname{grad}_j(U)=(\partial U /\partial x_1^j,\partial U/\partial x_2^j,\partial U/\partial x_3^j)$.

Show that the equations of motion can be written $m_jX_j''=-\operatorname{grad}_j(U)$. Note we already know $m_1X_1''=gm_1m_2 X_2-X_1/|X_2-X_1|^3$, $m_2X_2''=gm_1m_2 X_1-X_2/|X_2-X_1|^3$.

I started writing out $\operatorname{grad}_j(U)$ given $U$, but I am not getting a negative gradient in the end, only positive... I'm not sure where the negative sign comes from.

share|cite|improve this question

I am not sure of the signs in the OP. In any case:

$$f(X_1,X_2):=\frac{1}{|X_2-X_1|}=\frac{1}{\sqrt{\sum_{i=1}^3 (x^1_i-x^2_i)^2}}. $$


$$\frac{\partial f}{\partial x^1_j}=-\frac{1}{2\left(\sum_{i=1}^3 (x^1_i-x^2_i)^2\right)}\cdot 2 (x^1_j-x^2_j)=-\frac{x^1_j-x^2_j}{\sum_{i=1}^3 (x^1_i-x^2_i)^2}, $$


$$\frac{\partial f}{\partial x^2_j}=\frac{1}{2\left(\sum_{i=1}^3 (x^1_i-x^2_i)^2\right)}\cdot 2 (x^1_j-x^2_j)=\frac{x^1_j-x^2_j}{\sum_{i=1}^3 (x^1_i-x^2_i)^2}, $$ and similarly for all other partial derivatives.

Then we have

$$m_1\frac{d^2}{dt^2} (X_1)_j=-(\operatorname{grad}_1(U))_j=gm_2\frac{x^1_j-x^2_j}{\sum_{i=1}^3 (x^1_i-x^2_i)^2}, $$


$$m_2\frac{d^2}{dt^2} (X_2)_j=-(\operatorname{grad}_2(U))_j=-gm_1\frac{x^1_j-x^2_j}{\sum_{i=1}^3 (x^1_i-x^2_i)^2}, $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.